The Utility of Visual and Olfactory Maize Leaf Cues in Host Finding by Adult Spodoptera frugiperda (Lepidoptera: Noctuidae) - Jie Liu; Mariam Tallat; Gensong Wang; Guoping Li; Haowen Zhang; Xujin Wu; Hongbo Qiao; Xincheng Zhao; Hongqiang Feng (Plants)
The fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) (FAW), is an invasive and destructive polyphagous pest that poses a significant threat to global agricultural production. The FAW mainly damages maize, with a particular preference for V3–V5 (third to fifth leaf collar) plant stages in northern China. How the FAW moth precisely locates maize plants in the V3–V5 stage at night remains unclear. The aims of this study were to evaluate the visual and olfactory cues used by the FAW to identify its host plant, maize, in order to select attractants with better trapping efficacy. Hyperspectral analysis of maize plants at different growth stages using the ASD Fieldspec 4 spectrometer was performed using mimics (moths or maize leaves sealed with transparent plastic sheets) and black cloth-covered plants for single visual and single olfactory attraction experiments. Gas chromatography–mass spectrometry (GC-MS) was used to analyze volatiles emitted from V3–V5 stage maize leaves. Volatile organic chemicals (VOCs) were screened using electroantennography (EAG) and Y-tube. Attractor efficacy was validated using mimics + VOCs. Results showed very little variance in the spectral reflectance curve of the maize at different growth stages. Fifteen VOCs were identified in the V3–V5 stage leaves of three different maize varieties, of which cis-3-hexenyl acetate and myrcene were found in relatively high concentrations in these maize varieties. The frequency of visits attracted by single visual stimuli was significantly lower than that attracted by single olfactory or olfactory + visual cues. The attractiveness of foliar cis-3-hexenyl acetate increased as its concentration decreased. The combination of mimics + cis-3-hexenyl acetate (1 ng/μL) increased host detection efficiency and stimulated mating behavior. These results indicate that the nocturnal insect FAW primarily uses olfactory cues for host identification, with visual cues serving as a complementary modality. The synergistic effect of olfactory and visual cues increases the efficiency of host recognition. We found that cis-3-hexenol acetate at a concentration from maize leaves is a reliable olfactory signal for the FAW. When using host plant VOCs as attractants to control adult FAWs, the role of visual cues must be considered.